2016
DOI: 10.1039/c6ra01272h
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of upconversion nanoparticles in primary hippocampal cultures

Abstract: The research demonstrated that upconversion nanoparticles (UCNPs) are toxic to nervous cells. The cytotoxic severity depends on surface modification of UCNPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Although ligand-free lanthanide-doped nanoparticles are known to induce a decreased cell viability due to intracellular ATP deprivation in the live cells, little study is reported to investigate the neurotoxicity effects of the bare nanoparticles in vitro . [ 8 9 ] However, almost these studies used silica-coated rare-earth nanoparticles to study their biological toxicity in a short-term period. This could not reveal their toxicity in the practical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ligand-free lanthanide-doped nanoparticles are known to induce a decreased cell viability due to intracellular ATP deprivation in the live cells, little study is reported to investigate the neurotoxicity effects of the bare nanoparticles in vitro . [ 8 9 ] However, almost these studies used silica-coated rare-earth nanoparticles to study their biological toxicity in a short-term period. This could not reveal their toxicity in the practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Furthermore, Vedunova et al . [ 9 ] found that bare rare-earth nanoparticles are toxic to hippocampal cells in vitro . It is well known that ATP is the most important neurotransmitter in the mouse brain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] In addition, Maria et al . [ 17 ] found that bare rare-earth nanoparticles (RENPs) are toxic to hippocampal cells in vitro . So far, most reported studies have focused on the in vitro toxicity assays; however, the fate of RENPs circulating in the blood vessels and tissues in vivo is much more complicated.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite a wide range of existing nanomaterials, few of them meet the above criteria. Recent studies reveled that some types of NPs provide cytotoxic effects to the human organism, especially to the nervous system [5]. Therefore, it is so important to evaluate biosafety of the emerging NPs for brain cells and tissues.…”
Section: Introductionmentioning
confidence: 99%